Flash MX 2004 games : art to ActionScript - Lever, Nik, 1958- (Focal Press, 2004)
As a designer using Flash you will see how you can apply your creative skills to the many stages of game production and produce your own interactive games with this versatile package. Creating games for mobile devices is now also covered! As an animator you will be able to add interactive functionality to your own animation and produce a game. As a web developer you will see how to make the best use of the sophisticated development environment Flash offers for the production of both artwork and code to create low bandwidth, animated web content that sells! The free CD-Rom includes all the code.